KEANEKARAGAMAN JENIS BEGONIA (Begoniaceae) LIAR DI JAWA BARAT - Deden Girmansyah (Research Center for Biology-Indonesian Institute of Sciences, 2008)
A taxonomic study of the wild genera of Begonia Blume Begoniaceae) in West Java was conducted based on morphological characters. Nine known species (Begonia areolata Miq., Begonia isoptera Dryander, Begonia lepida Blume, B. longifolia Blume, B. multangula Blume, B. muricata Blume, B. repanda Blume, B. robusta Blume and B. tenuifolia Dryander) and one new species Begonia sp. was discovered. An identification key and information about potential uses of West Java's Begonia are described. Beside as ornamental plants, Begonia can be used for medicinal plant such as B. isoptera for spleen diseases.",